Phenology of particle size distributions and primary productivity in the North Pacific subtropical gyre (Station ALOHA). Issue 11 (18th November 2015) - White, Angelicque E.; Letelier, Ricardo M.; Whitmire, Amanda L.; Barone, Benedetto; Bidigare, Robert R.; Church, Matthew J.; Karl, David M.
Abstract: The particle size distribution (PSD) is a critical aspect of the oceanic ecosystem. Local variability in the PSD can be indicative of shifts in microbial community structure and reveal patterns in cell growth and loss. The PSD also plays a central role in particle export by influencing settling speed. Satellite‐based models of primary productivity (PP) often rely on aspects of photophysiology that are directly related to community size structure. In an effort to better understand how variability in particle size relates to PP in an oligotrophic ecosystem, we collected laser diffraction‐based depth profiles of the PSD and pigment‐based classifications of phytoplankton functional types (PFTs) on an approximately monthly basis at the Hawaii Ocean Time‐series Station ALOHA, in the North Pacific subtropical gyre. We found a relatively stable PSD in the upper water column. However, clear seasonality is apparent in the vertical distribution of distinct particle size classes. Neither laser diffraction‐based estimations of relative particle size nor pigment‐based PFTs was found to be significantly related to the rate of 14 C‐based PP in the light‐saturated upper euphotic zone. This finding indicates that satellite retrievals of particle size, based on particle scattering or ocean color would not improve parameterizations of present‐day bio‐optical PP models for this region. However, at depths of 100–125 m where irradiance exerts strong control on PP, we do observe a significant linear relationship between PP and the estimated carbon content of 2–20 μm particles. Key Points: Particle size is not correlated to productivity in the surface mixed layer of Station ALOHA Seasonal changes in the vertical distribution of particle size classes are apparent The carbon content of 2–20 μm particles is positively related to productivity rates at the DCM